Odpowiedzi

2010-03-08T18:50:16+01:00
B)2x-2=7-x
2x+x=7+2
3x=9/:3
x=3
c)10=4-2x
2x=4-10
2x=-6/:2
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-1,5
e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7/*(-1)
t=-7
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0≠0
i)(x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20/:(-5)
x=-4
2010-03-08T18:57:00+01:00
B)2x-2=7-x
2x+x=7+2
3x=9 /:3
x=3
c)10=4-2x
2x= 4-10
2x=-6 /:2
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=3 /:(-2)
x= -1,5
e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7 /:(-1)
t=-7
g)-(4+x)=2(3-x)
-4-x=6=x
2x=10 /:2
x=5
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18
0=0
rownanie tozsamosciowe(ma wiele rozwiazan)
i)(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20
x=-4